Immune status and lymphocyte apoptosis in women with arterial hypertension and metabolic disturbances - S. A. Frid; A. A. Karpov; I. A. Tuktarova; N. N. Kurchatova (Российский кардиологический журнал, 2008)
Lymphocyte apoptosis and functional activity were studied in 60 women with arterial hypertension and metabolic disturbances (AH) and 60 women with isolated systolic AH (ISAH). Cell apoptosis was assessed by flow cytometry method (propidium iodide technique). In AH patients, in contract to ISAH participants, T and B-lymphocyte deficiency was observed, and lymphocyte proliferation after mitogenic stimulation was reduced. There was a substantial inverse correlation between peripheral blood lymphocyte count and various apoptosis markers, as well as apoptosis associations with the levels of insulin resistance, obesity and dyslipidemia in AH women.